PD-L1 and tumor-infiltrating CD8+ lymphocytes are correlated with clinical characteristics in pediatric and adolescent pituitary adenomas - Shi, Mengwu; Song, Yifu; Zhang, Yaochuan; Li, Longjie; Yu, Juanhan; Hou, Ana; Han, Sheng (Frontiers in Endocrinology, 2023)
Objective To investigate the levels of tumor-infiltrating CD8+ lymphocytes (CD8+ TILs) and the expression of programmed cell death receptor ligand 1 (PD-L1) in the tumor microenvironment (TME) of pediatric and adolescent pituitary adenomas (PAPAs) and analyze the correlation between their levels and the clinical characteristics. Methods A series of 43 PAPAs cases were enrolled over a period of 5 years. To compare the TME of PAPAs and adult PAs, 43 PAPAs cases were matched with 60 adult PAs cases (30 cases were between 20 and 40 years old, and 30 cases were older than 40 years) for main clinical characteristics. The expression of immune markers in PAPAs was detected by immunohistochemistry, and their correlation with the clinical outcomes was analyzed using statistical methods. Results In the PAPAs group, CD8+ TILs level was significantly lower (3.4 (5.7) vs. 6.1 (8.5), p = 0.001), and PD-L1 expression (0.040 (0.022) vs. 0.024 (0.024), p < 0.0001) was significantly higher as compared with the older group. The level of CD8+ TILs was negatively correlated with the expression of PD-L1 (r = −0.312, p = 0.042). Moreover, CD8+ TILs and PD-L1 levels were associated with Hardy (CD8, p = 0.014; PD-L1, p = 0.018) and Knosp (CD8, p = 0.02; PD-L1, p = 0.017) classification. CD8+ TILs level was associated with high-risk adenomas (p = 0.015), and it was associated with the recurrence of PAPAs (HR = 0.047, 95% CI 0.003–0.632, p = 0.021). Conclusion Compared with the TME in adult PAs, the TME in PAPAs was found to express a significantly altered level of CD8+ TILs and PD-L1. In PAPAs, CD8+ TILs and PD-L1 levels were associated with clinical characteristics.